2019
DOI: 10.1002/jeab.539
|View full text |Cite
|
Sign up to set email alerts
|

Baseline training sequence affects speed of emergent conditional discriminations

Abstract: We examined the effects of baseline training sequence on the emergence of conditional discriminations in an intraverbal naming task. Thirty-two college students were randomly assigned to two groups. The tact-intraverbal (TI) group first learned to vocally tact eight visual stimuli using a unique verbal label for each stimulus, and then to intraverbally relate four pairs of verbal labels. The intraverbal-tact (IT) group received the same training but in the opposite sequence. Both groups then received a match-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…In addition, such knowledge could assist with instructional design, for example, in the context of equivalence‐based instruction (EBI) protocols (e.g., Fienup & Critchfield, 2011). The purpose of the present study was to explore the reliability and generality of the training sequence effect reported by Petursdottir et al (2019) in the intraverbal naming task. The first experiment aimed to replicate the original study with modifications intended to improve baseline retention and MTS accuracy.…”
Section: Step 1: Vocal Tact Training Step 2: Vocal Intraverbal Training Step 3: Match‐to‐sample Testmentioning
confidence: 77%
See 3 more Smart Citations
“…In addition, such knowledge could assist with instructional design, for example, in the context of equivalence‐based instruction (EBI) protocols (e.g., Fienup & Critchfield, 2011). The purpose of the present study was to explore the reliability and generality of the training sequence effect reported by Petursdottir et al (2019) in the intraverbal naming task. The first experiment aimed to replicate the original study with modifications intended to improve baseline retention and MTS accuracy.…”
Section: Step 1: Vocal Tact Training Step 2: Vocal Intraverbal Training Step 3: Match‐to‐sample Testmentioning
confidence: 77%
“…In Experiment 1, we modified the task and the training procedures in several ways from Petursdottir et al (2019). Specifically, we decreased the number of stimulus pairs from four in the previous study to three, increased the stringency of the mastery criterion for vocal baseline training, and altered the visual stimuli with the intention of making them more discriminable and reducing the likelihood of responding based on physical similarity (based on reports of some participants in the previous study).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…He also taught us how to be effective teachers. To those familiar with Jack's work, it is clear how his molecular approach to understanding behavioral regulation has shaped how we conduct our empirical investigations on verbal behavior, stimulus control, and derived stimulus relations (see Miguel, 2018; Petursdottir et al, 2019). We will never forget Jack's teachings or his sharp sense of humor, uninhibitedness, and most of all, his big heart.…”
mentioning
confidence: 99%